2022
DOI: 10.1002/fsn3.2867
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic treatment of Dendrobium officinale polysaccharide enhances antioxidant and anti‐inflammatory activity in a mouse D‐galactose‐induced aging model

Abstract: Utilization of the biological macromolecule Dendrobium officinale polysaccharide (DOP) as a functional ingredient is limited by its high intrinsic viscosity and molecular weight. The goal of the present study was to improve rheological properties of DOP by ultrasonic treatment. Such a treatment resulted in the degradation of DOP and consequent reduction of rheological properties. Among DOP samples treated with ultrasonication at low (L), medium (M), and high (H) power intensities (25, 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Cortical and subcortical micro-infarcts, scattered white matter disorders have all been connected to these processes. These injuries resulted in demyelination and axonal damage [1][2][3][4]. In addition, the ischemic damaging of the neuronal cells and the development of cerebral micro-hemorrhages of venous origin facilitate neurodegenerative disorders and dementia [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Cortical and subcortical micro-infarcts, scattered white matter disorders have all been connected to these processes. These injuries resulted in demyelination and axonal damage [1][2][3][4]. In addition, the ischemic damaging of the neuronal cells and the development of cerebral micro-hemorrhages of venous origin facilitate neurodegenerative disorders and dementia [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, people try to find the best natural ingredient to treat these diseases and to improve quality of life. There is a growing interest in herbal remedies because of their effectiveness, minimal side effects, and relatively low cost [ 32 , 33 ]. D. officinale is a traditional Chinese herbal medicine, and its flower has been reported to be a source containing a large number of phenolic components [ 20 , 34 ], which are of great value in serving potential food functions.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of NPs having regulation on Nrf2 antioxidant pathway from herbs, M w values of them have been determined to range from 2.273 to 2,617 kDa ( 41 , 54 56 ). The polysaccharides were composed of fucose (Fuc), ribose (Rib), mannose (Man), glucose (Glc), arabinose (Ara), galactose (Gal), rhamnose (Rha), xylose (Xyl), glucuronic acid (GlcA), galacturonic acid (GalA), glucosamine (GlcN), and/or galactosamine (GalN) ( 18 , 56 58 ). Moreover, Glc, Ara, Gal, and Rha were four monosaccharide types widely discovered in the polysaccharides ( 18 , 41 , 54 , 55 , 57 62 ).…”
Section: Structural Features Of Nps Having Regulation On Nrf2 Antioxi...mentioning
confidence: 99%
“…Animals experiments have demonstrated that NPs from herbs could regulate Nrf2 antioxidant pathway for liver protection ( 14 , 36 , 41 , 54 , 57 , 67 , 116 , 120 , 147 153 ), kidney protection ( 21 , 59 , 154 157 ), lung protection ( 20 , 158 ), neuroprotection ( 22 , 121 ), cardioprotection ( 124 , 159 ), gastrointestinal protection ( 16 , 40 , 48 , 127 , 128 , 160 , 161 ), anti-oxidation ( 15 , 47 , 162 164 ), anti-diabetic ( 56 , 58 , 135 , 146 , 165 , 166 ), anti-aging ( 18 , 68 , 84 , 167 ), anti-inflammation ( 23 ), anti-depression ( 25 ), anti-cancer ( 168 ), and improving reproductive function ( 169 , 170 ), as implied in Table 1 .…”
Section: Regulation Of Nps On Nrf2 Antioxidant Pathway For Health-pro...mentioning
confidence: 99%
See 1 more Smart Citation